A Retrospective Study on English Teachers' Strategies to Improve Students' Reading Comprehension - Apri Nola Sitanggang; Dicky Pratama; Erikson Saragih; Madina Madina (English Education Study Program Faculty of Teacher Training and Education, 2022)
Reading is a complex cognitive process from deciphering symbols to obtaining meaning. Although there is a lot of research on reading comprehension by teachers in Indonesia, there is still very little research on teacher strategies in reading comprehension to improve students' reading skills. This study aims to understand how teachers practice reading instruction, how they are assessed, and the strategies teachers use when teaching students to read. The research data were analyzed using qualitative data analysis techniques, namely: data collection, data reduction, analysis and data extraction. closing. This study uses qualitative methods and survey design. From the results of the research we have done, observations of teachers by giving questionnaires via a google form, so from these results we can conclude that the average of the 10 teachers we studied emphasized more strategies for giving practice and also reading practice, from both of these things the teacher mentioned that it is the most effective in improving the ability of students in reading skills, namely the teacher familiarizes his students with reading as a habit of problems that arise from the method used by the teacher when his students have difficulty in reading. The results of the second study with the formulation of the problem of what the students should do to improve their reading ability, which depends on the teacher, and what strategy the teacher will use to improve the student's abilities. practice to students as the main goal to facilitate better students' reading skills. The results of data collection from all the collected questionnaires can be concluded that about 85% of teachers prefer the type of practice or exam using the multiple choice method in reading because reading is more effective and efficient if the multiple choice technique is used. This test is a learning ability test that requires a good understanding because the test is a summary of the definitions of reading so this test is very good to use to improve student's reading comprehension.